Consumer and Market Study in Southwest and West Nile Refugee-Hosting Areas in Uganda - International Finance Corporation (Washington, DC, 2022)
The International Finance Corporation (IFC) commissioned a consumer and market study to explore economic activities, employment trends, consumption levels, and consumer preferences of refugees and host communities in Uganda’s largest refugee-hosting areas in the Southwest and West Nile regions. The study covers a gap in existing research on the economic situations of forced displacement, which is often conducted from a humanitarian perspective and rarely offers the private sector view. The study presents the refugees’ economic activities in their distinct roles as consumers, producers, suppliers, and salaried workers from the view of a private sector firm entering the market. It builds on earlier research conducted by the Uganda Investment Authority, in partnership with the United Nations Development Program (UNDP), which produced investment profiles for refugee-hosting districts. The report is divided into eight chapters. Chapter one introduces the study. Chapter two outlines the study methodology. Chapter three provides socioeconomic baseline data, such as educational attainment, employment, and income, comparable by region and population group (refugees versus host communities). Chapter four explores access to telecommunication and financial services. Chapter five analyzes household consumption expenditure, the volume of economic activity, consumer preferences, and access to finance and telecommunication services. Chapter six discusses findings from the business survey. Chapter seven briefly looks at agricultural value chains in the Southwest and West Nile. Chapter eight presents investment opportunities in the refugee-hosting districts for the private sector.